1981
DOI: 10.1002/1520-6807(198104)18:2<174::aid-pits2310180211>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the PPVT-R and WISC-R with urban educable mentally retarded students

Abstract: Comparisons of the revised PPVT (PPVT-R) and the WISC-R were made with 67 EMR students. Significant differences were found between the PPVT-R mean standard scores and Verbal, Performance, and Full Scale IQs. The PPVT-R did not correlate significantly with the WISC-R scales or subtests, suggesting the tests are measuring different abilities.The Peabody Picture Vocabulary Test (PPVT; Dunn, 1959) has been widely used by psychologists, speech and hearing specialists, and educators for over 20 years. The PPVT is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This revised Peabody (PPVT-R) has attracted much research attention, with studies of concurrent validity of the PPVT-R and the McCarthy Scales (Ferrari, 1980;Gullo & Mcloughlin, 1982;Naglieri, 1981), the PPVT and the PPVT-R with normal preschool children (Choong & McMahon, 1983;Naglieri & Naglieri, 1981), with gifted children (Karnes, McCallum, & Bracken, 1982;Pedriana & Bracken, 1982), with autistic children (Ferrari, 1980), and with urban educable mentally retarded students (Prasse & Bracken, 1981). In an interesting cross-cultural study, McCallum and Bracken (1981) found no significant differences between scores on the two forms (L and M) of the PPVT-R for whites, males, females, and the total group, but noted that "black preschool children may systematically earn higher scores on Form M than on Form L" (p.424).…”
supporting
confidence: 85%
“…This revised Peabody (PPVT-R) has attracted much research attention, with studies of concurrent validity of the PPVT-R and the McCarthy Scales (Ferrari, 1980;Gullo & Mcloughlin, 1982;Naglieri, 1981), the PPVT and the PPVT-R with normal preschool children (Choong & McMahon, 1983;Naglieri & Naglieri, 1981), with gifted children (Karnes, McCallum, & Bracken, 1982;Pedriana & Bracken, 1982), with autistic children (Ferrari, 1980), and with urban educable mentally retarded students (Prasse & Bracken, 1981). In an interesting cross-cultural study, McCallum and Bracken (1981) found no significant differences between scores on the two forms (L and M) of the PPVT-R for whites, males, females, and the total group, but noted that "black preschool children may systematically earn higher scores on Form M than on Form L" (p.424).…”
supporting
confidence: 85%
“…While these findings are consistent with Naglieri (1981) , they appear contrary to Prassee and Bracken's (1981) report of no significant PPVT-R/WISC-R correlations. However, they are not.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have examined the relationship between the PPVT-R and intelligence tests. Prassee and Bracken (1981) report that the PPVT-R was not correlated significantly with the WISC-R's Verbal, Performance, or Full Scale I& scores and yielded a significantly lower mean score for a sample of mentally retarded children. The difference in mean scores between the Peabody and intelligence tests is consistent with previous findings with the PPVT, but in the opposite direction; the PPVT tended to overestimate and Prassee and Bracken found that the PPVT-R underestimated I& scores.…”
mentioning
confidence: 99%
“…In a study by Naglieri (1981) formance .27, and Motor .23). These correlations were much higher than those between the PPVT and MSCA in Taylor's (1979) Prasse and Bracken (1981) compared the performances of 67 Black, Hispanic, and White EMR students on the PPVT-R and the Wechsler Intelligence Scale for Children-Revised -WISC-R (Wechsler, 1974). The children ranged in age from 7-3 to 15-8 years.…”
Section: Peabody Picture Vocabulary Test -Revisedmentioning
confidence: 99%
“…Naglieri (1981) warned that the PPVT-R should not be used as a substitute for the MSCA, and, additionally, he has noted that the PPVT-R may be more appropriate as a brief measure of verbal comprehension. Breen (1981) and Prasse and Bracken (1981) compared standard scores from the Wechsler Intelligence Scale for Children-Revised -WISC-R (Wechsler, 1974) with standard scores of the PPVT-R and found that the PPVT-R underestimates the intellectual abilities of preschool children. They concluded that the PPVT-R should not be used as an intelligence measure.…”
Section: Naglieri (1981) Has Compared the Ppvt-r With The Mccarthy Scmentioning
confidence: 99%